2009
DOI: 10.1086/599328
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Enhances Histoplasmosis by Immunosuppression of the Host

Abstract: The effect of methamphetamine on the host response to an opportunistic pathogen has not been extensively described. Methamphetamine is a major public health and safety problem in the United States. Chronic methamphetamine abuse is associated with a 2-fold higher risk of human immunodeficiency virus infection and, possibly, additional infections. Histoplasma capsulatum is a dimorphic fungus that is endemic in the Midwest of the United States and that causes respiratory and systemic disease, particularly in indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
102
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 38 publications
8
102
1
Order By: Relevance
“…This is also consistent with the hypothesis that internalization of yeast by macrophage strictly via CR3 inhibits the respiratory burst (5,36,47). These findings are also supported by our recent observation that IgG2b levels were significantly increased in histoplasmosis in mice treated with methamphetamine, and these mice have accelerated disease and increased mortality (24). Hence, certain antibodies may be detrimental, especially compromising the capacity of macrophages to combat this intracellular invader.…”
Section: Discussionsupporting
confidence: 76%
“…This is also consistent with the hypothesis that internalization of yeast by macrophage strictly via CR3 inhibits the respiratory burst (5,36,47). These findings are also supported by our recent observation that IgG2b levels were significantly increased in histoplasmosis in mice treated with methamphetamine, and these mice have accelerated disease and increased mortality (24). Hence, certain antibodies may be detrimental, especially compromising the capacity of macrophages to combat this intracellular invader.…”
Section: Discussionsupporting
confidence: 76%
“…METH’s ability to alkalize acidic organelles may inhibit antigen presentation, impairs phagocytosis, and likely compromises the immune response to pathogen inactivation [6062]. For example, it has been showed that METH inhibits endosomal acidification in macrophages [6062]. A neutral pH of endosomes has been shown to have beneficial effects for pathogens during infection of macrophages [63].…”
Section: Immunomodulatory Functions Of Meth May Modulate Hiv-1 Infectmentioning
confidence: 99%
“…A neutral pH of endosomes has been shown to have beneficial effects for pathogens during infection of macrophages [63]. In addition, METH has also been reported to destabilize the capacity of infected macrophages to regulate their intracellular milieu [6062]. In macrophages endosomal trafficking plays critical roles in HIV-1 replication [64].…”
Section: Immunomodulatory Functions Of Meth May Modulate Hiv-1 Infectmentioning
confidence: 99%
“…High TNF-α production in the blood directly alters the permeability of the BBB suggesting that this cytokine plays an important role in the induction of meningitis by inhibiting the expression of TJs. Although previous studies have shown that elevated TNF-α levels increase the BBB permeability [12][13][14] and the essential role of zyxin on bacterial dissemination, 15,16 this is the first study that shows that TNF-α reduces zyxin expression on the surface of brain endothelial cells exacerbating Hi CNS transmigration using the TH mechanism leading to increased mortality.…”
mentioning
confidence: 78%